Stereospecific reversible deactivation radical polymerization of biomass‐based acrylates for precise control of tacticity and molecular weight. Issue 3 (2nd November 2016) - Tanaka, Hitoshi; Kibayashi, Tatsuya; Okuda, Kazuya; Kashihara, Shoichi
ABSTRACT: Reversible deactivation radical polymerization (RDRP) of biomass‐based acrylates, ( S )‐ and ( R )‐2‐isopropyl‐5‐methylene‐1, 3‐dioxolan‐4‐ones ( S ‐MiPDO and R ‐MiPDO), was successfully performed to produce a well‐defined polymer with simultaneously controlled tacticity and molecular weight, and low dispersity ( Đ < 1.3). In particular, meso triad ( mm ) of the polymer was continuously controlled as designed from 28.1% to about 100% by changing the molar ratio of S ‐MiPDO/ R ‐MiPDO in feed. In kinetic studies, the rate of RDRP was strongly influenced by the stereostructures of the propagating radical, and it was much lower in isospecific RDRP than atactic one in reversible chain transfer catalyzed polymerization (RTCP) in contrast to atom transfer radical polymerization (ATRP) where the rate would not change regardless of the tacticity. Increase of molecular weight and low Đ of the polymer were also observed in reversible addition‐fragmentation chain transfer (RAFT) polymerization of MiPDO. In addition, block copolymers including stereoblock copolymers were feasibly synthesized by RTCP of styrene and methyl methacrylate using poly(MiPDO) prepolymer. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 445–456 Abstract : Simultaneous perfect control of tacticity, molecular weight, and dispersity was achieved in the stereospecific reversible deactivation radical polymerization of biomass‐based acrylates. In such a polymerization, polymer isotacticity ( mm ) was continuously controlled as designed from 28.1% to about 100% only by changing the ee value of the charged monomer. Block copolymerization using a prepolymer produced the stereoblock, hydrophobic, and hydrophilic copolymers.